Pelaksanaan Pendidikan Politik Melalui Pembelajaran Pendidikan Pancasila dan Kewarganegaraan untuk Meningkatkan Kesadaran Politik Siswa - Rahman, Asmika; Suharno, Suharno (Universitas Negeri Malang, 2019)
This article describes the implementation of political education through learning Pancasila and Civic Education learning to increase the political awareness of students in Abu Bakar Integrated Islamic High School Yogyakarta. This research used descriptive qualitative method. This study gathers data use interviews, observation, and documentation. The results showed that the implementation of political education through learning Pancasila and Civic Education learning was using the 2013 Curriculum and KTSP, the development of the material, and the use of learning models. Factors that support the implementation of political education are the application of a national curriculum, professional teachers, extracurricular activities, and the availability of facilities.